Sentences And Verbs In The Poetry Of Ali Bin Al-Jahm And Their Poetic Connotations: Rhetorical And Statistical Stylistics Study/ الجمل والأفعال في شعر علي بن الجهم ودلالاتها الشعرية : الدراسة البلاغية والأسلوبية الإحصائية - Darlin, Muhammad Zakaria; Dani, Abd. Rahim (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
The types of sentences and verbs are among the essential linguistic elements that contribute to building meaning within literary texts, especially in classic Arabic poetry, which relies on the precision of expression and strength of connotation. This research aims to study the rhetorical implications and interpretations of sentences and verbs in the poetry of Ali ibn al-Jahm by analyzing his use of verbs and their role in embodying meanings and poetic purposes based on the theory of statistical stylistics. The research relies on the rhetorical descriptive-analytical method, where sentences are classified according to their types (nominal and verbal), and verbs are classified according to their types in terms of tense (past and present), affirmation (affirmative and negative), and structure (known and unknown), and analyzing their impact on depicting the emotions and ideas expressed by the poet. The research also discusses the relationship between the choice of verbs and the general context of the poem, with a focus on rhetorical techniques using the statistical stylistic approach that enhances poetic connotation. The results reveal that Ali ibn al-Jahm used verbs with artistic precision that reflect his psychological states and profound intellectual stances, making his poetry a rich model for studying the interaction between linguistic structure and literary meaning. This is evident in the frequency of nominal sentences in his poetry—indicative of permanence—less common than verbal sentences—indicative of movement and the renewal of events. We also found a predominance of past tense verbs over present tense verbs in many of his poems and a predominance of the active voice over the passive voice. All these phenomena indicate his love and longing for the past days with the Caliph al-Mutawakkil during his lifetime in the Abbasid Empire.